Study on pattern of gynaecological malignancies at Saveetha Medical College and Hospital, Tamil Nadu, India - Ethirajan, Shanthi; D., Mohanapriya; C., Aarthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The burden of malignancy and deaths due to it are rising worldwide. In women gynaecological malignancies are among the most common cancers. This study was undertaken to study the pattern and relative frequencies of gynaecological malignancies among women admitted in the Department of Gynaecology, at Saveetha Medical College and Hospital, Tamil Nadu. Methods: This is a retrospective observational study done at the department of Saveetha Medical College and Hospital over a period of two years from September 2015 to September 2017. Case records of women admitted in the Department of Gynaecology and diagnosed to have gynaecological malignancy were retrieved from the department of medical records. Information regarding demographic details, site of malignancy, histopathology of malignancy was analysed and expressed as percentages. Results: During the study period 49 cases of gynaecological malignancies were reported. Out of 49 cases, 36 cases were cancer cervix, followed by 7 cases of ovarian malignancy and 6 cases of cancer of uterine corpus. The mean ages of cancer cervix, ovary and corpus uteri were 51.1, 53.3 and 47.2 years respectively. All women were multiparous in the study. One third of women were premenopausal. Women with cancer cervix and corpus uteri commonly presented with irregular bleeding, post-menopausal bleeding and white discharge per vaginum. Ovarian cancers presented commonly with abdominal pain and distension. Squamous cell carcinoma of cervix was the commonest histopathology seen. Adenocarcinoma and epithelial cancer was the commonest histopathology seen in endometrial and ovarian cancer respectively. Conclusions: Cancer cervix was the commonest gynaecological malignancy in the study population followed by ovarian and uterine malignancies.